Digital note-taking applications for digital native learners - Karjo, Clara Herlina (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Note-taking is an indispensable skill to ensure success in learning. Note-taking can be done traditionally by pen and paper or digitally using ICT devices. Digital notes can be done using certain digital notetaking applications, which can be obtained freely or commercially. This paper intends to discover the university students’ perception of the use of digital note-taking apps for their study during online learning sessions and their preferences for note-taking methods which are suitable for them. The data were taken from the online questionnaire distributed to 64 university students at a private university who were conveniently chosen as the participants for this study. The results showed that the students preferred making digital notes using their digital devices to writing them on paper. However, they did not use any specific note-taking apps, typing the notes using Microsoft Word instead. It was more practical and easier to use for them. The findings implied that note-taking is important no matter the device used to do it.